Peningkatan Kualitas Sumber Daya Manusia (SDM) UMKM Melalui Pelatihan Kepemimpinan dan Inovasi Bisnis: Pengabdian - Rena Augia Putrie; Yamolala Zega; Marlina; Junaidi; Muhammad Affar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effectiveness of leadership and business innovation training in improving the quality of human resources (HR) in MSMEs. The implementation of the activities was carried out through several stages, including preparation, program socialization, training, mentoring, and evaluation. The results of this activity indicate that leadership and business innovation training has proven effective in improving the quality of human resources (HR) in MSMEs. Participants showed an increase in understanding of leadership concepts by up to 93% and successfully implemented more structured communication, data-driven decision-making, and more visionary business planning. In terms of innovation, participants became more proactive in trying out product, service, and digital marketing updates, which resulted in increased operational efficiency and business attractiveness. This indicates that the training can trigger real changes in business management and development in a more focused and sustainable manner.